Anatomical and Physiological Characteristics of the Digestive Tract in Childhood - , Luiz Antonio Del Ciampo; , Ieda Regina Lopes Del Ciampo (Archives of Current Research International, 2020)
Nutrition is an act of fundamental survival in the human being's relational process with the environment. It is, instinctive in the first weeks of life and then becomes a learned behavior that counts on the participation of all organs and senses. The child needs nutrients in adequate quantity and quality during his growth and development, and depends on a system capable to receivieng, metabolize, absorb and excrete the components of the diet. This article presents some characteristics of the child's digestive system that must be known to provide him with adequate food for his anatomical and physiological abilities.